2015
DOI: 10.1063/1.4936369
|View full text |Cite
|
Sign up to set email alerts
|

Si quantum dots in silicon nitride: Quantum confinement and defects

Abstract: Luminescence of amorphous Si quantum dots (Si QDs) in a hydrogenated silicon nitride (SiNx:H) matrix was examined over a broad range of stoichiometries from Si3N2.08 to Si3N4.14, to optimize light emission. Plasma-enhanced chemical vapor deposition was used to deposit hydrogenated SiNx films with excess Si on Si (001) substrates, with stoichiometry controlled by variation of the gas flow rates of SiH4 and NH3 gases. The compositional and optical properties were analyzed by Rutherford backscattering spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
11
1
2
Order By: Relevance
“…The origin of luminescence in SiN systems has been extensively studied in the past for their applications in Si-based optoelectronic devices. PL emission from SiN films in the visible range has been previously attributed to both the quantum confinement effect of carriers inside Si QDs embedded in the SiN and radiative defect–related states in SiN or at Si-QD/SiN interface structures ( 40 , 41 ). PL peaks exhibiting spectral shifts with annealing temperature and SiN composition were typically associated with the Si QDs.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of luminescence in SiN systems has been extensively studied in the past for their applications in Si-based optoelectronic devices. PL emission from SiN films in the visible range has been previously attributed to both the quantum confinement effect of carriers inside Si QDs embedded in the SiN and radiative defect–related states in SiN or at Si-QD/SiN interface structures ( 40 , 41 ). PL peaks exhibiting spectral shifts with annealing temperature and SiN composition were typically associated with the Si QDs.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have been reported on Si-NCs embedded in silicon dioxide (SiO 2 ) [12,13,14]. Based on the quantum confinement theory [15,16,17], the correlation between the photoluminescence (PL) properties and the size of the nanocrystals has been established. Control over all three parameters (size, density, spherical shape) can be reached by depositing thin alternating layers of stoichiometric and Si rich dielectrics in the form of a superlattice (SL).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to study the luminescence characteristics of SiN x O y film. Some reported results showed that the luminescence mechanism of SiN x O y film is generally divided into three types: defect-state radiation composite luminescence [46], band-tail (BT) radiation composite luminescence [47] and quantum dot radiation composite luminescence [48].…”
Section: Performance Of Sinxoy Filmmentioning
confidence: 99%